(untitled) (American & British Studies Annual, 2013)
Tracey Scott Wilson’s theater play Buzzer premiered in February 2012, well into the final year of Barack Obama’s first term as President of the United States. The play deals with one fragile concept that stood at the beginning of Obama’s victory in 2008, the notion of a “post-racial” America, that is, an America whose citizens have gone beyond the frames of thought defined by race. A significant part of Obama’s campaign was based on the idea that race could be transcended not only in politics, but also in people’s everyday lives. This paper attempts to examine how Tracey Scott Wilson’s play tackles the intersection of political slogans, policies and strategies with the world of emotions, personal and familial history, and racial identity. My analysis will focus on racial and post-racial theories, the frailty of race transcendence, and the far-reaching consequences of social schemes, such as neighborhood gentrification and revitalization, or class and race segregation. Underneath the structures that constrain them, Wilson’s characters desire to engage in a post-racial utopia, but are unable to transcend their racially and socially ingrained identities.